Pemetaan Penggunaan Lahan Desa Lendiang Liang Nayuq dengan Memanfaatkan Data Pendaftaran Tanah Sistematis Lengkap Tahun 2022 - Herlan Herlan; Nia Kurniadin; Ahmad Aris Mundir Sutaji; Shabri Indra Suryalfihra (Politeknik Pertanian Negeri Samarinda, 2024)
The research was motivated by the implementation of Complete Systematic Land Registration (PTSL) activities in Lendiang Liang Nayuq Village in 2022 to provide guarantees of legal certainty or rights to land owned by the community. PTSL activities have an impact on land use in Lendiang Liang Nayuq Village. Thus, it is necessary to utilize the results of these measurements to map land use. The aim of this research is to determine the area of Lendiang Liang Nayuq Village, the area of land that has been developed in the form of settlements, public facilities, plantations, and Cultivation Rights (HGU) in Lendiang Liang Nayuq Village, Siluq Nurai District, West Kutai Regency. The method used in this research is direct measurements in the field using GPS Geodetic HI-target v60 to obtain measuring field coordinates in the form of land use and village administrative boundaries. Next, digitization is carried out using GIS software. The results of this research showed that the number of fields measuring PTSL 2022 results in Lendiang Liang Nayuq Village, Siluq Ngurai District, West Kutai Regency was 314 fields, consisting of housing, public facilities, and plantations. Meanwhile, the land use area is 0.03% of the built-up land area in the form of settlements, 0.66% plantations, 0.09% public facilities, 25.51% Cultivation Rights and the remaining 73.71% is non-PTSL 2022 land.